Effect of processing on the antioxidant activity of aerial yam (Dioscorea bulbifera L.cv.) - Dognidon, Kenneth Andrew R.
ABSTRACT The effect of boiling, baking and pressure cooking on the antioxidant activity of aerial yam was studied to provide baseline data for the study of antioxidants in aerial yam. Methanolic extracts of aerial yam were analyzed for total phenolic content, free radical scavenging activity, reducing power, ferrous ion chelating ability and total antioxidant activity. Comparing the processing methods, phenolic content was highest in baked yam (59.20 mg GAE/100 g dry matter) and lowest in boiled yam (48.41 mg GAE/100 g dry matter). Baked yam also had the highest free radical scavenging activity activity (EC50 = 3.19 mg/mL) while pressure cooked yam had the lowest (EC50 = 5.63 ± 0.10). The former also had the highest reducing power (EC50 = 3.66 mg/mL) and ferrous ion chelating ability (EC50 = 34.53 mg/mL) while boiling has the lowest in both the reducing power (EC50 = 4.80 mg/mL) and ferrous ion chelating ability (EC50 = 57.31 mg/mL). Baking also had the highest inhibitory action against linoleic acid oxidation (62.18%) at 10 mg/mL sample concentration. The extracts had lower radical scavenging activity, reducing power, ferrous ion chelating ability and total antioxidant activity compared to the standards alpha-tocopherol and ethylene diamine tetraacetic acid (EDTA). Regardless of the method, processing caused a significant (P < 0.05) decrease on the given parameters when compared to the fresh yam extract except for the decrease caused by baking on the total antioxidant activity. Significant correlation (P < 0.05) was observed between total phenolic content and the EC50 values for DPPH free radical scavenging activity (r = -0.949), reducing power (r= -0.919), ferrous ion chelating ability (r = -0.644) and total antioxidant activity (r=0.783). Radical scavenging activity (r= -0.808) and ferrous ion chelating ability (r=-0.870) were also found to have a significant (P<0.05) correlation with the total antioxidant activity of the aerial yam extracts.